Taking Control and 'Moving On': How Young People Turn around Problematic Transitions from Out-of-Home Care. - Guy Johnson; Philip Mendes (Social Work & Society, 2014)
In this paper we draw on in-depth interviews with 59 young people (aged between 18-24) who had experienced a volatile transition from out-of-home care. As a group they had a high number of placements in care, many had experienced physical and/or sexual abuse prior to, or while they were in care, most had histories of substance misuse, and all had experienced homelessness at some point since leaving care. However, we found that the circumstances of just over half (n=32) had significantly improved and they appeared to be successfully navigating a route to independence. We argue that a notable feature of those who were 'moving on' was the agency and, more specifically, the positive focus and direction of their agency. Those who were 'moving on' expressed a strong sense of the need to take control and of wanting something better and we identified five pivotal moments or experiences that encouraged young people to actively seize control over their lives and their circumstances -stable housing; addressing substance abuse; improved family relationships; meaningful relationships with professional support; and finding work. These five factors are often interlinked, but whatever the catalyst(s), the resulting turnaround in the young people's lives was pronounced. We draw a connection between these positive turning points, and the importance of policy and legislation that enables ongoing support for care leavers beyond the initial transition from care.